Struktura, kompetencje i działalność prawotwórcza Organizacji Międzynarodowego Lotnictwa Cywilnego - Polkowska, Małgorzata (Studia Prawa Publicznego, 2026)
This article concerns the International Civil Aviation Organization (ICAO) as the administrator and legislator for international civil aviation. Aviation is largely international in nature. It could not expand without global uniformity of regulations, standards, and procedures for air navigation. The ICAO’s structure and tasks, as defined by the 1944 Chicago Convention on the Elimination of Civil Aviation, ensure access to air transport in a peaceful and safe manner. The regulations that constitute the organization serve this purpose. These are not only international treaties but also technical annexes, the aim of which is to harmonise the rules of air navigation. These annexes are created by the Air Navigation Commission and recommended to the ICAO Council for approval. The standards and recommendations contained in the ICAO technical annexes (in whole or in part) are incorporated into the national laws of many States Parties to the Convention. They cover a range of issues such as aviation personnel licensing, air traffic, airports, flight operations, and the transport of dangerous goods. They are among the most important international regulations created for the States Parties to the Chicago Convention, and their proper implementation and application guarantees aviation safety. The ICAO’s legislative functions are largely limited to highly technical issues of an apolitical nature, while its legislative objectives are largely determined by technical progress in the field of aviation. The requirements for compliance with ICAO regulations are flexible enough to address the economic and technical issues that each member state may face.